Ugly Mug - "Dalton, Annie" (Puffin Books: London, 1996)
Ned finds it very difficult to come to terms with his parents' divorce and is terrified at the prospect of a weekend visit to his dad's new flat. But when he and his dad find a baby sparrow that has fallen out of its nest, it is caring for "Ugly Mug" that helps to bring the two of them close again.
Keywords: children fiction junior-Book